2016
DOI: 10.1111/desc.12406
|View full text |Cite
|
Sign up to set email alerts
|

Predicting writing development in dual language instructional contexts: exploring cross‐linguistic relationships

Abstract: This study examined whether decoding and linguistic comprehension abilities, broadly defined by the Simple View of Reading, in grade 1 each uniquely predicted the grade 6 writing performance of English-speaking children (n = 76) who were educated bilingually in both English their first language and French, a second language. Prediction was made from (1) English to English; (2) French to French; and (3) English to French. Results showed that both decoding and linguistic comprehension scores predicted writing ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Other researchers (August, Carlo, Dressler, & Snow, 2005; Mancilla-Martinez & Lesaux, 2010) have reached this conclusion, but the specificity of the evidence generated from this study makes this call all the more pressing. Indeed, our results align with recent work by Savage, Kozakewich, Genesee, Haigh, and Erdos (2017) who found that early (grade 1) language screening of English-French bilingual students in the primary grades predicted later (grade 6) writing outcomes, suggesting that language development instruction may represent a promising mechanism by which to support reading and writing outcomes among bilingual learners.…”
Section: Discussionsupporting
confidence: 90%
“…Other researchers (August, Carlo, Dressler, & Snow, 2005; Mancilla-Martinez & Lesaux, 2010) have reached this conclusion, but the specificity of the evidence generated from this study makes this call all the more pressing. Indeed, our results align with recent work by Savage, Kozakewich, Genesee, Haigh, and Erdos (2017) who found that early (grade 1) language screening of English-French bilingual students in the primary grades predicted later (grade 6) writing outcomes, suggesting that language development instruction may represent a promising mechanism by which to support reading and writing outcomes among bilingual learners.…”
Section: Discussionsupporting
confidence: 90%
“…Thirdly, future studies should include a measure or a range of measures of oral language. Although existing studies typically report weak to moderate correlations between measures of oral language and the length and quality of children's written products, the role of oral language in written text production should not be minimized as recent evidence suggests that oral sentence fluency supports written text generation over time and across languages (Savage et al, 2017). Fourthly, we depict development using cross-sectional data, longitudinal data are needed to fully establish the direction of the relationship between the different variables.…”
Section: Limitationsmentioning
confidence: 97%
“…Oral formulated sentence skills, tested with a standardised assessment, predict written text generation over time and across languages (Savage, Kozakewich, Genesee, Erdos, & Haigh, 2017) and predict, as well, written grammatical skills in children with DLD and Autism Spectrum Disorder (Dockrell, Ricketts, Charman, & Lindsay, 2014). Written sentence generation has been reported to be a sensitive and specific measure to identify struggling writers and is strongly predicted by oral sentence skills (Dockrell et al, 2019).…”
Section: Dld Oral Language and Verbs Studies Of Early Lexical Develmentioning
confidence: 99%
“…Multiple linear regression was used to explore which factors predicted children's written use of verbs. Building on previous research (Dockrell, Connelly, & Arfè, 2019;Savage et al, 2017) The final sample of children used in this study was selected to ensure that the two writing prompts used were balanced across each of the groups and so consisted of 90 children. The children comprised three groups: n = 30 children with a diagnosis of DLD (20 boys and 10 girls) with a mean age of 9;11 (range 9;5 to 10;6), n = 30 matched for CA with a mean age of 9:10 (range 9:6 to 10:5) and n = 30 LAb group with a mean chronological age of 8:1 (range 6:8 to 8:10) who were matched with the DLD group for raw scores on an oral sentence production task.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation